Fat Grafting to Improve Results of Facelift: Systematic Review of Safety and Effectiveness of Current Treatment Paradigms. (7th January 2020) - Molina-Burbano, Felipe; Smith, J Michael; Ingargiola, Michael J; Motakef, Saba; Sanati, Paymon; Lu, Jocelyn; Taub, Peter J; Hill, Michael E
Abstract: Background: Autologous fat grafting is a helpful supplement to facelift surgery that helps to combat age-related volume loss of facial structures. Despite the widespread prevalence of combined facelift and fat-grafting, significant procedural variation exists between providers. Objectives: The primary purpose of this systematic review was to study the efficacy and complication rates of facelift with lipofilling compared with facelift alone. Methods: A systematic review of the Cochrane Library and MEDLINE databases as completed was undertaken to identify all clinical reports of fat grafting combined with facelift surgery based on the following key terms: ("fat grafting" OR "lipotransfer" OR "lipofilling" OR "fat transfer") AND ("facelift" OR "rhytidectomy" OR "SMASectomy" OR "facial rejuvenation"). Data on techniques, outcomes, complications, and patient satisfaction were collected. Results: The systematic review was performed in April 2017. In total, 248 articles were identified for review. After application of exclusion criteria, 15 primary studies were included in this review. Various facelift techniques were reported, including deep-plane or sub–superficial musculoaponeurotic system (SMAS) facelift, SMAS facelift, modified minimal access cranial suspension lift, component facelift, midface lift, SMAS plication, SMAS-stacking/SMASectomy, and SMASectomy. The most common locations of fat graft injection included the nasolabial folds, tear troughs, temporal regions, midface/cheek/malar eminence, marionette groove, lips, and ear lobes. The addition of fat grafting to facelift surgery resulted in significant improvements in facial volume and aesthetic assessments. Conclusions: Combined facelift and fat grafting is a safe and efficacious means to simultaneously address age-related ptosis and volume loss. Further research is required to validate and improve existing treatment modalities. Level of Evidence: 3: